Evaluation of the role of rhizobacteria in controlling root-knot nematode infection in Lycopersicon esculentum plants by modulation in the secondary metabolite profiles. Issue 6 (21st October 2019) - Khanna, Kanika; Jamwal, Vijay Lakshmi; Sharma, Anket; Gandhi, Sumit G; Ohri, Puja; Bhardwaj, Renu; Al-Huqail, Asma A; Siddiqui, Manzer H; Marraiki, Najat; Ahmad, Parvaiz
Abstract: Environmental stress imposes negative impacts on the growth and development of the crop plants. The present study was designed to assess the effect of plant growth-promoting rhizobacteria (PGPR) ( Pseudomonas aeruginosa and Burkholderia gladioli ) on plant pigments and phenolic compounds in 10-day-old root-knot nematode (RKN)-infected Lycopersicon esculentum seedlings. The levels of different osmoprotectants and organic acids were also evaluated in nematode-infected L. esculentum seedlings. Our results revealed that nematode-infected seedlings had reduced levels of plant pigments (chlorophyll (70.5 %), carotenoids (64.8 %) and xanthophylls (34.3 %)) and enhanced levels of phenolic compounds (total phenols (40.3 %), flavonoids (80.9 %), anthocyanins (28.9 %) and polyphenols (366.1 %)), osmoprotectants (total osmolytes (15.3 %), total carbohydrates (54.9 %), reducing sugars (45.3 %), trehalose (94.5 %), glycine betaine (59.01 %) and proline (69.6 %)) and (citric acid (28.4 %), fumaric acid (18.16 %), succinic acid (179.9 %) and malic acid (21.7 %)). The levels of these metabolites increased after inoculation with P. aeruginosa and B. gladioli. The expression of genes encoding different enzymes pertaining to phenols and organic acid metabolism was also studied. The expression of genes was elevated in nematode-infected plants, i.e. CHS (chalcone synthase) by 1.32-folds, PAL (phenylalanine ammonia lyase) by 1.16-folds, CS (citrate synthase) by 1.6-folds, SUCLG1 (succinyl-CoA ligase) by 1.19-folds, SDH (succinate dehydrogenase) by 1.92-folds, FH (fumarate hydratase) by 2.4-folds and malate synthase ( MS ) by 1.26-folds and further upregulated after PGPR inoculation. This study demonstrates the importance of PGPR in managing nematode infection in plants through alteration in the synthesis of different secondary metabolites in plants. Abstract : Plants are exposed to different pathogens that affect crop productivity globally. The current study was designed to explore eco-friendly methods to control root-knot nematode (RKN) infection by the use of rhizobacterial strains ( Pseudomonas aeruginosa and Burkholderia gladioli ). These strains were inoculated in infected tomato plants and the extent of their infection was noted by assessing different plant parameters such as photosynthetic pigments, phenolic compounds, osmoprotectants and organic acids. Transcriptomic analysis was also conducted using qRT–PCR to evaluate the expression levels of genes associated with phenol and organic acid metabolism ( CHS, PAL, CS, SUCLG1, SDH, FH, MS ). This study advocates the best use of plant growth-promoting rhizobacteria in alleviating RKN infection in tomato plants.